Bone Marrow-Derived Mesenchymal Stem Cell (BM-MSC) Sebagai Sumber Alternatif Sel Blastema Terhadap Regenerasi Anggota Tubuh - Kuntum Sureda (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
Limb regeneration is initiated by blastema cells (BC) and related genes that are only present in mammals confined to the distal fingertips of the phalangeal terminals and neonates. If amputated to proximal phalangeal, regeneration will fail due to lack of blastema cells (BC) in adults and difficulty in isolating and using blastema cells (BC) from neonates. BM-MSC has succeeded in increasing its ability to regenerate various wound tissue and its healing properties, because of this BM-MSC is used as an alternative cell source that produces blastema cells (BC). The original blastema cells (BC) that isolated from neontus and blastema cells (BC) in BM-MSC were compared to the ability of colony formation, cell proliferation, alkaline phosphatase activity (ALP), calcium supply, and osteogenic gene expression. The ability to form colonies was significantly higher in BM-MSC compared to original BC (P <0.05). Alizarin red stain (ARS), calcium and ALP tests show higher levels of mineral deposition in BM-MSCs. The qRT-PCR analysis revealed cells from both sources were ready to differentiate into mesodermal lineages. The rate of expression of osteblastic markers shows the capasity of bone differences is higher at BM-MSC at all time points.